A fast method for the determination of lead in honey samples using stabilizer-free silver nanoparticles - Bittar, Dayana Borges [UNESP]; Catelani, Tiago Augusto [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier, 2018)
A sensitive, rapid and robust method based on the use of stabilizer-free silver nanoparticles was developed for lead detection in honey. Silver nanoparticles were synthesized without the presence of any stabilizers using silver nitrate and sodium borohydride as precursors where the latter was applied as reducing agent. The optimization of the experimental variables (AgNO3 and NaBH4) for the formation of the nanoparticles was carried out using varying volumes of these solutions. Spectrophotometric measurements at 393 nm showed a linear working range between 0.0500 and 0.167 mg L− 1 lead (R = 0.994), with limits of detection (LOD) and quantification (LOQ) of 0.0135 and 0.0451 mg L− 1, respectively. The proposed method proved to be a significantly sensitive mechanism for lead detection in honey samples.
Keywords: Contamination; Honey; Lead; Silver nanoparticles